Experimental observations consistent with a surface tension model of gliding motility of Myxococcus xanthus. - Dworkin, M (1983)
We have presented experimental evidence to support the model that gliding motility of Myxococcus xanthus is driven by surface tension. (i) Motility is inhibited by the addition of sufficient exogenous, nontoxic surfactants to swamp out the cells' own surfactant gradient. (ii) M. xanthus does not move polystyrene latex beads over its surface. (iii) Motility is prevented by elimination of an interfacial surface tension either by embedding the cells in soft agar or by placing them at an agar-aqueous interface. (iv) Wild-type cells excrete surfactant, whereas two nonmotile mutants excrete reduced amounts.